Utilizing Mobile Technology: WhatsApp Group Chats as a Tool to Enhance Students' Engagement in ESP Learning - Pratiwi, Nindyah; Wijayanti, Anita (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
In line with the development of globalization, English is increasingly in demand, especially among students. This is because English is a fundamental competency with an international scope. In order to improve their skills, students need more time to study, and since the onset of Covid-19, online learning through WhatsApp has become a trend. This application allows teaching and learning to not only become easier but also encourages greater participation from students, helping them achieve their learning goals. This study found that students have a positive perception of using WhatsApp groups for ESP discussion learning. This research contributes valuable empirical evidence, providing continuous support for the collaboration of ESP courses via WhatsApp. However, this study has limitations, including a small sample size and general findings, indicating the need for further research to explore its long-term impact and the more specific implementation of technology-based learning.